2012
DOI: 10.1073/pnas.1111628109
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methyltransferase G9a methylates the transcription factor MyoD and regulates skeletal muscle differentiation

Abstract: Skeletal muscle cells have served as a paradigm for understanding mechanisms leading to cellular differentiation. The proliferation and differentiation of muscle precursor cells require the concerted activity of myogenic regulatory factors including MyoD. In addition, chromatin modifiers mediate dynamic modifications of histone tails that are vital to reprogramming cells toward terminal differentiation. Here, we provide evidence for a unique dimension to epigenetic regulation of skeletal myogenesis. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 29 publications
9
162
1
Order By: Relevance
“…5D). We then tested the impact of Sharp-1 sumoylation on MyoD transcriptional activity, which is inhibited by Sharp-1 (10,18). 10T1/2 cells were transfected with the myogenin promoter reporter pMyog-Luc (22) along with MyoD alone or together with Sharp-1 or Sharp-1 2KR.…”
Section: Sharp-1 Is Sumo-modified-we Have Recently Reported Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…5D). We then tested the impact of Sharp-1 sumoylation on MyoD transcriptional activity, which is inhibited by Sharp-1 (10,18). 10T1/2 cells were transfected with the myogenin promoter reporter pMyog-Luc (22) along with MyoD alone or together with Sharp-1 or Sharp-1 2KR.…”
Section: Sharp-1 Is Sumo-modified-we Have Recently Reported Thatmentioning
confidence: 99%
“…Consistent with the recruitment of G9a, enrichment in H3K9me2 is apparent at MyoD target promoters in Sharp-1-overexpressing cells. Moreover, MyoD methylation at lysine 104 (Lys-104) is also enhanced by G9a (10,18). Thus, inhibition of G9a expression or activity partially rescues Sharp-1-dependent repression of myogenesis (17).…”
mentioning
confidence: 99%
“…52 In the case of myogenin promoter, the molecular mechanism of repression would involve the interference with the activity of chromatin-bound MyoD through the cooperation with other histone modifications. 60 It has also been reported that G9a, in addition to methylate histone H3, also methylates the MyoD protein, 61 indicating that the relationship between G9a, H3K9me2, and MyoD functions is very complex. On the other hand, we found that the presence of high levels of H3K9me2 at KvDMR1 correlates with the failure of MyoD to access chromatin, thus suggesting an additional way by which this histone modification affects MyoD-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond histones, G9a/GLP have been shown to methylate a plethora of non-histone targets, including the tumor suppressor p53, SIRT1, Reptin, MyoD, Wiz, CDYL and several chromatin regulators (50,67,77,88,120). Moreover, G9a methylates itself and this modification mediates its interaction with HP1 and CDYL (127).…”
Section: H3k9 Methyltransferases Structure and Enzymatic Activitymentioning
confidence: 99%
“…Moreover, it has been shown that PRC2 plays critical roles to preserve the transcriptional identity of skeletal muscle stem cells by repressing non-muscle cell lineage-specific genes (5,54). Interestingly, recent works have also implicated G9a/GLP in MyoD target gene repression (77,100). Particularly, GLP has been recently found in the PRDM16 complex (100), a wellknown potent inhibitor of muscle differentiation (133), to mediate H3K9me2 deposition and silencing of muscle specific genes, thus favoring the adipogenic differentiation of a population of Myf5 + progenitors, known to be the common precursors of brown adipocytes and muscle cells (133), suggesting a previously unappreciated role for GLP in regulating muscle progenitors lineage choice.…”
Section: Role In Adult Stem Cell Differentiationmentioning
confidence: 99%